1994
DOI: 10.1016/s0006-3495(94)80599-5
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous 280 MHz EPR imaging of rat organs during nitroxide free radical clearance

Abstract: A radio frequency (RF) (280 MHz) electron paramagnetic resonance (EPR) spectroscopy and imaging apparatus has been used to localize a pyrrolidine nitroxide free radical in the rat abdomen and thorax. The nitroxide 2,2.5.5,-tetramethylpyrrolidine-1-oxyl-3- carboxylic acid (PCA) had a whole body monoexponential decay with half-life of 13.3 +/- 0.7 (n = 4), 19.4 +/- 0.2 (n = 3), and 23 +/- 2 (n = 6) min for 1, 2, and 3 mmol/kg PCA, respectively. Up to seven one-dimensional longitudinal projections were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 21 publications
1
43
0
Order By: Relevance
“…In vivo EPR imaging was first performed using an exogenous, synthetic, and stable free radical that was locally administered to small animals. 27 With the recent improvement of low-frequency EPR instrumentation and the synthesis of better imaging agents, many exciting results have been obtained. For example, imaging of the abdominal region of mice treated with lipopolysaccharide demonstrated the presence of spin trapped NO; 28 three-dimensional spatial and two-dimensional spectral-spatial imaging of charcoal in the GI tract of a living mouse demonstrated the oxygen gradient in the organ; 29 imaging of rat brain under kainic acid-induced seizure indicated that the oxidative stress in the hippocampus and striatum is enhanced, but is not in cerebral cortex; 30 and imaging of tumor-bearing legs of mice showed oxygen concentration images with high resolution in space (1 mm) and pO 2 ($3 torr).…”
Section: Epr Imagingmentioning
confidence: 99%
“…In vivo EPR imaging was first performed using an exogenous, synthetic, and stable free radical that was locally administered to small animals. 27 With the recent improvement of low-frequency EPR instrumentation and the synthesis of better imaging agents, many exciting results have been obtained. For example, imaging of the abdominal region of mice treated with lipopolysaccharide demonstrated the presence of spin trapped NO; 28 three-dimensional spatial and two-dimensional spectral-spatial imaging of charcoal in the GI tract of a living mouse demonstrated the oxygen gradient in the organ; 29 imaging of rat brain under kainic acid-induced seizure indicated that the oxidative stress in the hippocampus and striatum is enhanced, but is not in cerebral cortex; 30 and imaging of tumor-bearing legs of mice showed oxygen concentration images with high resolution in space (1 mm) and pO 2 ($3 torr).…”
Section: Epr Imagingmentioning
confidence: 99%
“…For example, a charged nitroxide will not cross the plasma membrane and thus can be used to measure the concentration of oxygen in the extracellular compartment; a neutral nitroxide will be distributed throughout the intracellular and extracellular environments [44,45] . Nitroxides have also played a key role in the field of EPRI, where numerous organs of the rat have been investigated [46][47][48] . EPRI of the abdominal region of mice REVIEW ORGANIC CHEMISTRY treated with lipopolysaccharide was achieved in the presence of spin-trapped NO.…”
Section: Water-soluble Paramagnetic Materialsmentioning
confidence: 99%
“…One-dimensional EPR spectra of a nitroxyl radical, TEM- (11). After that, 2D or 3D EPRI studies in mice or rats were reported from several groups (2,4,41,103). A variety of EPRI systems and equipment for biologic samples were developed by each group for their experimental purpose (3, 13-15, 24, 29, 47, 82, 83, 95).…”
Section: Conventional Cw Eprimentioning
confidence: 99%